A Descriptive Correlational Study of Cancer Patients at the National Institute in Misurata: دراسة وصفية ارتباطية على عينة من مرضى الأورام بالمعهد القومي بمصراتة. (Journal of Academic Research, 2026)
The aim of this study was to identify the levels of both death anxiety and psychological resilience among a sample of cancer patients at the National Institute in the city of Misurata. The study also sought to examine differences in the levels of these two variables according to demographic factors, including gender, age, and marital status. The study sample consisted of 49 cancer patients who were selected using a purposive sampling method.To achieve the objectives of the study and answer its research questions, several statistical techniques were employed, including means, standard deviations, Cronbach’s alpha coefficient, Spearman’s correlation coefficient, and the independent samples t-test.The findings revealed a low level of death anxiety and a high level of psychological resilience among cancer patients at the National Institute in Misurata. Furthermore, the results indicated that there was no statistically significant correlation between death anxiety and psychological resilience among the study participants.Keywords: Death Anxiety, Psychological Resilience, Cancer Patients.